RELATIONSHIP BETWEEN LEAD AND CADMIUM LEVELS IN BLOOD AND REFRACTORY CHRONIC CONSTIPATION AMONG IRANIAN CHILDREN - GHARIBSHAHI,Nasrin (2021)
ABSTRACT BACKGROUND: There is limited research examining reasons causing refractory chronic constipation (RCC) in children. The effects of lead (Pb) and cadmium (Cd) exposures on this condition have been even less clear. However, some related factors may contribute to evaluation of blood lead levels (BLLs) and blood cadmium levels (BCLs). OBJECTIVE: The present study aimed to examine the relationship between Pb and Cd exposures and RCC in children living in the city of Ahvaz, Khuzestan Province, in Southwestern Iran. METHODS: This study was performed on a total number of 48 children aged 2-13 years, including 36 medically-diagnosed RCC cases and 12 controls referring to a pediatric clinic in the city of Ahvaz. Their BLLs and BCLs were then determined using a graphite furnace atomic absorption spectrophotometer. The data from the researcher-designed questionnaire were also recoded and the related risk factors were analyzed through Spearman’s correlation and logistic regression analysis. RESULTS: The findings revealed that the geometric means of Pb and Cd in blood samples in the control group were 58.95 µg/dL and 0.45 µg/dL; respectively. These values in the case group were equally 45.26 µg/dL and 0.26 µg/dL; respectively. A significant difference was additionally observed between BCLs in the case and control groups (P<0.01). All children in both groups also had BLLs greater than the permissible limit endorsed by the World Health Organization (WHO) (≤10 µg/dL). On the other hand, 8.3% of the individuals in the case group and 33.3% of those in the control group had BCLs higher than the acceptable range mentioned by WHO (≤0.5 µg/dL). CONCLUSION: Pb and Cd exposures due to environmental pollution and susceptibility to heavy metals may not be associated with RCC in children living in the city of Ahvaz. Although this research was the first one providing data on BLLs and BCLs in children with RCC, the findings could be useful for designing future epidemiologic studies.